To find the distance between pair of points use the formula
\(\displaystyle\sqrt{{{\left({x}{1}-{x}{2}\right)}^{{2}}+{\left({y}{1}-{y}{2}\right)}^{{2}}}}\)

The given value is (3,-2) and (4,3)

so

x1=3

y1=-2

x2=4

y2=3

So after applying the formula PSK=sqrt((4-3)^2+(3-(-2))^2) =sqrt((4-3)^2+(3+2)^2)ZSK

\(\displaystyle{\left({4}-{3}\right)}^{{2}}={1}\)

PSK(3+2)^2=5^2 =sqrt(1+5)^2 =sqrt(1+25) =sqrt26ZSK

The given value is (3,-2) and (4,3)

so

x1=3

y1=-2

x2=4

y2=3

So after applying the formula PSK=sqrt((4-3)^2+(3-(-2))^2) =sqrt((4-3)^2+(3+2)^2)ZSK

\(\displaystyle{\left({4}-{3}\right)}^{{2}}={1}\)

PSK(3+2)^2=5^2 =sqrt(1+5)^2 =sqrt(1+25) =sqrt26ZSK